A study of lactate and pyruvate levels as reliable indicator of impaired tissue perfusion - Agarwal, Tarun; Jain, Veenu (International Journal of Research in Medical Sciences, 2016)
Background: Inadequate tissue perfusion leads to raised plasma lactate and pyruvate levels in human body due to anaerobic oxidation in state of stock. Till date, lactate and pyruvate levels have not been extensively used as an indicator for the detection of severity of stock and its outcome. Aims and Objective: This study is an attempt to co-relate Lactate and Pyruvate levels as reliable indicator of severity of impaired tissue perfusion and its outcome in shock patients. Methods: This is a retrospective analysis of a prospective study in which 172 patients were studied in different groups and randomization was done on first come first enrolment basis after having informed consent from the patient or attendants or both. The data collection and storage was done on pre-formed working Performa sheets. Results were analyzed by applying Students –‘t’ test. Results: It was found that Plasma lactate and pyruvate levels are excellent and reliable indicators of impaired tissue perfusion. Conclusions: The study concluded that an early rise in plasma lactate and pyruvate levels is seen in chock patients. Detection of these biochemical parameters value can be taken as a reliable prognostic indicator, which can influence the outcome in the management of shock.